Upaya Peningkatan Status Gizi Murid Sekolah Dasar Dengan Pemberian Vitamin A Dan Minum Susu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Vitamin A and protein calorie deficiency lead to the decrease of immunity, especially among children. This is due to the fact that they often suffering from diarrhea, cold and bronchitis. Among student of Primary School, the diseases altered to decreased of learning achievement because they are often do absent from to school. This study has been carried out to overcome nutrients deficiency and to increase learning achievement among student of Primary School in Sleman by giving vitamin A tablet and drinking milk. The sample were sixth grade of class, they were given a tablet of 600 IU vitamin A every week and drinking a glass of milk every morning for 8 weeks. After treatments, the statistical analysis showed that the nutrition status and learning achievement increased significantly (P < 0.05), along with the decrease of morbidity.